Spiral Fracture in Young Infant Causing a Diagnostic Dilemma: Nutritional Rickets versus Child Abuse - Sonia Kaushal; Manish Raisingani; Raphael David; Bina Shah (Case Reports in Pediatrics)
Fractures are uncommon in young, nonambulatory infants. The differential diagnosis includes nonaccidental injury (NAI) and metabolic bone disease, including rickets. While rickets typically present after six months of age, multiple cases have been reported in younger infants. We report a case of an 11-week-old male infant who presented with a spiral fracture of the humerus and no radiologic evidence of rickets. A detailed psychosocial assessment failed to reveal any risk factors for NAI. The patient had elevated alkaline phosphatase and PTH with low 25 hydroxyvitamin D and 1,25 dihydroxyvitamin D levels. Additionally, the mother was noncompliant with prenatal vitamins, exclusively breastfeeding without vitamin D supplementation, and had markedly low vitamin D levels 15 weeks postpartum. The biochemical data and history were consistent with rickets. Given the diagnostic dilemma, the working diagnosis was rickets and the patient was started on ergocalciferol with subsequent normalization of his laboratory values and healing of the fracture. These findings are consistent with nutritional rickets largely due to maternal-fetal hypovitaminosis D. This case highlights that in young infants rickets should be considered even in the absence of positive radiologic findings. Additionally, it illustrates the importance of maintaining adequate vitamin D supplementation during pregnancy and early infancy.